PROBLEMS OF ICT-BASED TOOLS ESTIMATION IN THE CONTEXT OF INFORMATION SOCIETY FORMATION - M. Shyshkina (Kherson State University, 2012)
The article describes the problems of improvement of quality of implementation and use of e-learning tools which arise in terms of increasing quality and accessibility of education. It is determined that those issues are closely linked to specific scientific and methodological approaches to evaluation of quality, selection and use of ICT-based tools in view of emergence of promising information technological platforms of these resources implementation and delivery.